Comparison of the output spectrum for four models of devices with crossed fields - Alfyorov, M.E.; Volovenko, M.V.; Moshchenko, I.O.; Nikitenko, O.M. (Radiotekhnika, 2023)
This paper considers four models of crossed-field devices: cylindrical magnetron, cylindrical magnetron diode, planar magnetron diode and planar magnetron. As is known, in crossed-field devices electrons move by cycloid-like trajectories and induced current arises. The spectral components of the induced current for every of the models are calculated. It has been found that the components of the induced current spectrum contain from one (planar magnetron diode) to eight (cylindrical magnetron diode) components. The calculated spectral components have been compared to the spectral components of the generation spectrum of the real device. Only one component whose frequency coincides with the cyclotron frequency was found in the induced current spectrum of the planar magnetron diode. The induced current spectrum in a planar magnetron has three components. These frequencies have a large difference with the frequency of magnetron generation for a microwave oven. Therefore, the models of the planar magnetron diode and the planar magnetron are not very suitable for simulating the operation of crossed-field devices. The induced current spectrum in a cylindrical magnetron diode contains eight components. The third harmonic is closest to the fundamental frequency of the microwave magnetron. In this case, the difference between the frequencies being compared is near 10 %. Therefore, the model of a cylindrical magnetron diode is not very suitable for modeling the operation of crossed-fields devices. Two components were found in the induced current spectrum of a cylindrical magnetron. The first harmonic is the closest to the fundamental frequency of the microwave magnetron. In this case, the difference between the frequencies being compared does not exceed 3 %. Such a small discrepancy between the calculated and real frequencies can be explained by the presence of a spatially periodic distribution of the electrostatic field. Thus, the cylindrical magnetron model is well suited for simulating the operation of crossed-fields devices.